Synthesis and properties of monometallic, homo- and heterobimetallic complexes based on {(η6-arene)RuCl}+ and {(η6-arene)OsCl}+ fragments with tetrathioether and tetraselenoether ligands - Levason, William; Marshall, Catherine; Ollivere, Luke P.; Reid, Gillian; Tsoureas, Nikolaos; Webster, Michael (Journal of Organometallic Chemistry, 2010)
The reaction of [Ru(η6-p-cymene)Cl2]2 with 2.0 mol equivalents of C(CH2SMe)4, C(CH 2SeMe)4, 1,2,4,5-C6H2(CH 2SMe)4 or 1,2,4,5-C6H2(CH 2SeMe)4 (L4) and [NH4][PF 6] in ethanol solution forms the [RuCl(η6-p-cymene) {κ2-L4}][PF6] complexes. Similar Os(II) complexes are obtained starting with [Os(η6-p-cymene)Cl 2]2. Treatment of [RuCl(η6-p-cymene) {κ2-L4}][PF6] with a further 0.5 mol equivalents of [Ru(η6-p-cymene)Cl2]2 or reaction of [Ru(η6-p-cymene)Cl2]2 directly with 1.0 mol equivalent of L4 forms the homobimetalllic [{RuCl(η6-p-cymene)}2{κ2κ ′2-L4}][PF6]2. Reaction of [OsCl(η6-p-cymene)-{κ2-C(CH2SeMe) 4}][PF6] with [Ru(η6-p-cymene)Cl 2]2 or [PtCl2(MeCN)2] affords the heterobimetallic [{OsCl(η6-p-cymene)}{RuCl(η6-p- cymene)}{κ2κ′2-C(CH2SeMe) 4}][PF6]2 and [{OsCl(η6-p- cymene)}{PtCl2}{κ2κ′2- C(CH2SeMe)4}][PF6] respectively. The complexes have been characterised by multinuclear NMR and IR spectroscopy and X-ray crystallography. The synthesis and properties of homomonometallic and homo-and hetero- bimetallic complexes based upon tetrathio-or tetraselenoether ligands with {(arene)MCl]+ units are described, and crystal structures reported for representative examples. © 2010 Elsevier B.V.
Keywords: Osmium; Ruthenium; Tetraselenoether; Tetrathioether